(untitled) (Sociologisk Forskning, 2018)
Who is theory? A norm-critical pedagogical perspective on sociological theory Sociological theory is a central part of the sociology discipline, and courses on sociological theory are found on all levels of university teaching in sociology at Swedish universities. However, while sociologists have successfully uncovered power structures in various domains of social life, we have been more reluctant to examine our own teaching practices. In particular, sociological theory has been pinpointed as an area where men’s dominance often perseveres. This is in stark contrast to international research on exclusion and inclusion in processes of canon formation, which shows how there have always been important sociological theorists who have not been white men, but that they have been more or less written out of history. Drawing on such international research on inclusion and exclusion in the construction of sociological theory, as well as on norm-critical pedagogy, and on a mapping of the curriculum at one of Sweden’s universities, this article identifies key aspects in the quest for a more inclusive curriculum.